Extrinsic Versus Intrinsic Benefits: Challenging Categories Used to Define the Value of Music in Schools - Alexander Hew Dale Crooke (Voices, 2016)
Increasing pressures to justify the value of music in schools over recent decades has led to the construction of three distinct areas of benefits: intrinsic (or musical) benefits, extrinsic benefits related to academic and/or cognitive development, and extrinsic benefits related to psychosocial wellbeing. While some argue these categories have been useful for identifying specific areas of value and enabling targeted advocacy approaches, others have challenged this segmented approach to justification. While the most strident point of contention stems from the perception that categories which champion non-musical (extrinsic) benefits have led to the devaluing of musical (intrinsic) benefits, others dispute the categories themselves. Such arguments question the ability to separate what have been categorised as musical and non-musical elements, particularly in relation to social and political elements. This paper aims to tease out the practicality of these existing categories, and in doing so, challenge their robustness in both form and definition. The argument is made that current attempts to separate the value of school-based music into distinct categories is not only unclear, but also unhelpful in areas of advocacy. This argument rests on the premise that musical participation affords opportunities to enrich human experience in holistic and integrated ways, and that categorisation serves to preclude this unique value.